On linear algebraic groups over pseudoglobal fields - Andriychuk, V. (Algebra and Discrete Mathematics, 2007)
Some properties of R–equivalence and weak approximation in linear algebraic group over global field are generalized to the case of linear algebraic group over an algebraic function field in one variable with pseudofinite constant field.